Physical Stability and Effectivity Comparison of Nanoemulsion and Nano-emulgel of Avocado Oil with Carbopol 940 Variation - Shabrina, Ayu (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Avocado oil (AV) contains of oleic acid that can prevent skin erythema. Nanoemulsion (NE) in a gel system (NG) is a one of a delivery system that increases the drug's effectivity. This study aimed to compare AV's stability and effectivity as anti-erythema in NE and NG with variations of carbopol 940. NE was made with 5% of AV and incorporated in carbopol 940 (for NG) with variations of 0.5 (F1);1 (F2), and 1.5% (F3). The samples were stored in a climatic chamber for 90 days at a temperature of 30 °C ± 2 °C RH 65% ± 5%. Samples were tested for organoleptic, pH, viscosity, particle size (PS), polydispersity index (PDI), and zeta potential (ZP). The samples were also tested based on in vitro SPF values and minimum erythema dose (MED). The results show that NE has a clear appearance whie NG showed a creamy texture. The physical parameters met the criteria for nanoemulsion delivery. F1 NG showed an increase in physical parameters, while F2 and F3 were stable for 90 days of storage. The SPF value of AV in NE and NG were not significantly different, yet the MED showed differences in each formula. Carbopol at a concentration of 0.5-1.5% can produce stable nano-emulgel. Avocado oil nanoemulsion showed better effectivity to prevent erythema than nano-emulgel.